If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -3x = 7x + -6 Reorder the terms: 10 + -3x = -6 + 7x Solving 10 + -3x = -6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 10 + -3x + -7x = -6 + 7x + -7x Combine like terms: -3x + -7x = -10x 10 + -10x = -6 + 7x + -7x Combine like terms: 7x + -7x = 0 10 + -10x = -6 + 0 10 + -10x = -6 Add '-10' to each side of the equation. 10 + -10 + -10x = -6 + -10 Combine like terms: 10 + -10 = 0 0 + -10x = -6 + -10 -10x = -6 + -10 Combine like terms: -6 + -10 = -16 -10x = -16 Divide each side by '-10'. x = 1.6 Simplifying x = 1.6
| y^2+12x+2y+20=0 | | 10*lgx=25 | | 10logx=25 | | 10*logx=25 | | (2x+6)+2x+x=35 | | a^2b^2+ab+a^2+b^2=0 | | -x^2-8x-14=0 | | 0=x^2-x(k+1)+2k+1 | | 4x+34=7x-8 | | 4x+3x+19=180 | | 0=x^2-(k+2)x+2k+1 | | 3/5(4x-5)+4.5= | | cos(sin(x))=65 | | 19x+12=2(9x-5) | | sin(x^2)=0.7 | | 20=0*0.10 | | 5x+x+20= | | P/5=32 | | 7x-y=-42 | | 13n-3/2n-10 | | x-3/6=x-7/4 | | y=8*x^2-11*x+9 | | 2ab-14ab=0 | | 2r-3s-2r-3s= | | 5x+3+7x-9=v | | 15n-14y-14n-14y= | | f(x)=8*t^3-33*t^2+27*t | | x^3+8x-12=0 | | x=ln(2a) | | 6.50x+1.50y=414 | | d+2d-8=34-3d | | 6x+10=8x-2 |